Foreign direct investment and the pollution in five ASEAN nations - Merican, Yasmine; Yusop, Zulkornain; Mohd Noor, Zaleha; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
We investigated the impact of FDI on pollution for Malaysia, Thailand, Indonesia, Singapore, and the Philippines- significant FDI recipients within the developing world in the last three decades- and the findings invite further questions. Our time-series analyses, employing the Autoregressive Distributive Lag (ARDL) technique suggest that FDI adds to pollution in Malaysia, Thailand, and the Philippines but not in Indonesia where FDI is inversely related to pollution, and Singapore where it proved insignificant.